2SPD-025 Acalabrutinib + obinutuzumab versus ibrutinib + obinutuzumab as first line in chronic lymphocytic leukemia. (23rd March 2022) - Claramunt García, R; Muñoz Cid, CL; Sánchez Ruiz, A; Pérez, E; Jiménez López, Y
Abstract : Background and importance: Acalabrutinib + obinutuzumab is authorised for the treatment of previously untreated patients with chronic lymphocytic leukemia (UPCLL), such as ibrutinib. Since comparative studies are not yet available, an indirect comparison (IC) between them could be of special interest. Aim and objectives: To establish, through an IC versus obinutuzumab + clorambucil, whether acalabrutinib + obinutuzumab and ibrutinib + obinutuzumab can be considered equivalent therapeutic alternatives (ETA) in efficacy in the treatment of UPCLL. Material and methods: A PubMed search of pivotal clinical trials (CTs) responsible for the authorisation of both drugs was performed. Progression-free survival (PFS) results were taken as the main variable for comparison. IC were performed using the Bucher method (indirect treatment comparisons calculator, Canadian Health Technology Assessment Agency) of UPCLL from both trials. The reference value used for the sample calculation in ibrutinib + obinutuzumab CT was hazard ratio (HR)=0.55 and HR=0.60 in acalabrutinib + obinutuzumab CT, therefore a delta (Δ) of 0.6 was set as the most clinically relevant value. With this value, acalabrutinib + obinutuzumab was compared with ibrutinib + obinutuzumab in PFS and the results were analysed to see if the confidence intervals (95% CI) were within the ±Δ interval. The methodology of the Spanish ETA-Guide 1 (a tool that allows assessment of the clinical equivalence of two or more drugs and position them) was applied. Results: Two CTs were found, one with acalabrutinib + obinutuzumab and another with ibrutinib + obinutuzumab, both against obinutuzumab + clorambucil as a common comparator. Both studies had a similar methodology. However, in the ibrutinib + obinutuzumab trial, patients with small lymphocytic lymphoma were included, although they were minority (5%). This limitation for IC was accepted. After applying the Bucher method, a HR=0.435 (95% CI 0.218 to 0.866) was obtained for acalabrutinib + obinutuzumab versus ibrutinib + obinutuzumab. According to the ETA-Guide, in the comparative efficacy of both drugs, a D position was obtained: graphically, the 95% CI was positioned almost completely within the ±Δ interval. Therefore, the difference is probably irrelevant. However, as treatment failure involves a serious prejudice for the patient, according to this guide they would be considered not ETA. Conclusion and relevance: According to the ETA criteria, acalabrutinib + obinutuzumab and ibrutinib + obinutuzumab could not be considered ETA, since after IC a greater benefit was observed with acalabrutinib + obinutuzumab. Nevertheless, safety and efficiency criteria should also be taken into account. References and/or acknowledgements: 1. Med Clin (Barc) 2014;143 (2):85–90. Conflict of interest: No conflict of interest